模拟退火算法在减速器优化设计中的应用 - 张礼兵; 吴婷 (Jixie chuandong)
Based on the theory of simulated annealing algorithm, the object mathematic model and the restriction condition of the reducer optimal design were established. The key technology of simulated annealing algorithm was expatiated and the examples showed the reducer Design can be optimized remarkably.